The effect of engine emission on canola biodiesel blends with TiO2. Issue 8 (17th November 2019) - Nithya, S.; Manigandan, S.; Gunasekar, P.; Devipriya, J.; Saravanan, W. S. R.
ABSTRACT: The role of nanoparticles and nanofluid additives for biodiesel has gained consistent position in the current trend as they contribute to increase the performance of the engine with lower emission. In addition, additives also help to increase the engine reliability and lifespan. In this work, the effects of canola biodiesel blends of 20% proportions with diesel were investigated at 100% of engine load. The fuel is tested in a multi-cylinder water-cooled direct ignition (DI) engine. There are numerous notable works on nanofluid; however, the addition of TiO2 nanoparticle as additive to produce canola biodiesel fuel is very limited. With the addition of the TiO2 nanoparticle on Canola biodiesel blend in the DI engine, the exhaust property of gases such as CO, HC and NO X is reduced. Furthermore, the combustion characteristics of the engine are improved. The canola biodiesel blends also resulted in lower NO x emission as well as low smoke.